UMP, DID sought Korean expertise on river management - UMP, PNC
Universiti Malaysia Pahang (UMP)’s Centre of Earth Resources & Research Management (CERRM) and Drainage and Irrigation Department (DID) jointly organised a seminar on managing river health at Seri Pacific Hotel in Kuala Lumpur on March 1, 2012.